INDONESIA'S ECONOMIC DEVELOPMENT POLICY AS IMPLEMENTATION OF PANCASILA AS THE IDENTITY OF INDONESIA - Muhammad Gunawan Wibisono; Atika Purnama; Fitri Al Istiqomah (Jurnal Transformasi Global, 2018)
Identity of Indonesian economic development has always become a focus within the period of Indonesian leader. Every leader has their own operation to drive the development of Indonesian economic and it can’t be consider indonesia has one economy development system which right or left. This paper is trying to discuss about Indonesia’s economic development system which cannot be said as a country that uses one of the two economic systems. By trying to analyze it from the development of the Indonesian economy from each era that connects it with the decision-making process of leaders which eventually becomes a economic system identity that only Indonesia has. The system called as Pancasila economic system which will explain here and it connection with Indonesia leader in making decision and identity of Indonesia itself.